Wind-tunnel investigation of the Ruck-A-Chucky suspension bridge - Peterka, Jon A., author; Bienkiewicz, Bogusz, author; Cermak, Jack E., author; Fluid Dynamics and Diffusion Laboratory, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1977)
A section model of the proposed Ruck-A-Chucky Bridge and a topographic model of its site were used in the wind tunnel study. Freely oscillating section models of the original and modified bridge decks were applied to investigate aerodynamic derivatives. Steady drag, lift and pitching moment were measured for the rigidly supported model. Wind parameters (velocity profiles and turbulence characteristics) for the bridge site were measured on the topographic model. Flow visualization for both the section and topographic model was used to determine nature of the flow field and detect regions of separation and vortex formation. The aerodynamic derivatives indicate stable behavior of the proposed bridge decks, although the smooth bridge deck (without fences and railings) shows slight coupling between flexural and torsional modes. Further analysis for the entire bridge, using the wind tunnel derived aerodynamic coefficients, is necessary to predict its overall aerodynamic stability.
CER77-78JEC-BB-JAP11.
For T. Y. Lin International.
July 1977.
Keywords: Suspension bridges -- Aerodynamics; Wind tunnel models